Penerapan Model Pembelajaran Teams Game Tournament Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas VI Sekolah Dasar - Risal M. Merentek; Yolanda A. Perori; Norma N. Monigir (Peneliti.net, 2023)
The purpose of this study was to improve social studies learning outcomes for class VI students at SD Negeri Sarongsong through the application of the Teams Game Tournament (TGT) learning model. The subjects of this research were the students of class VI at SD Negeri Sarongsong. This research is a classroom action research referring to the research design by Kemmis and Mc Taggart (in zainal aqib) with the following research procedures: planning, action, observation, and reflection stages used in two cycles. Data collection was carried out using direct observation of the learning process and tests. The data obtained from the learning process is calculated using the learning completeness formula, namely the number of scores obtained by students divided by the total score and then multiplied by one hundred percent. The results obtained by students at each stage of learning activities in cycle I were 67% and increased to 20.94% in cycle II of 87.94%. Seeing from the results of this study, it is suggested to the homeroom teacher that the application of the Teams Game Tournament (TGT) model can be used as an alternative or teacher's effort in improving student social studies learning outcomes